Adjuvant application of trastuzumab in HER2 positive breast cancer and impact on time to relapse - Dukic, Nikolina; Gojkovic, Zdenka; Vladicic-Masic, Jelena; Masic, Srdjan; Lalovic, Nenad; Popovic, Sladjana (Archive of Oncology, 2019)
Background: Of all breast cancers 20-25% are HER2 positive. Overexpression of HER2 protein on the surface of the malignant cell leads to excessive cell proliferation through different signaling pathways. Trastuzumab is a human monoclonal antibody that binds to domain IV of HER2 receptor and blocks signaling pathway for proliferation. The result is an improved prognosis for HER 2 positive breast cancer patients, even when compared to patients with other types of breast cancers. Methods: The study presents 74 women patients with early HER2 positive breast cancer who were previously operated (either radicaly or using breast conserving surgery), and received adjuvant chemo- and radiotherapy. Fourty four patients received adjuvant trastuzumab for one year, and 30 patients did not (control group). Observed time to relapse of the disease was 60 months. Results: There was a significant difference in survival in favor of the group that received trastuzumab (p<0.001). Application of trastuzumab also delayed relapse of the disease by 51.7%. No significant difference was observed between estrogen receptor positive and estrogen receptor negative cancers., In the control group there was a significant difference in relapse free survival in favor of estrogen and progesteron receptor positive tumors (p<0.001). Conclusion: Survival of patients with a HER2 positive breast cancer whose prognosis was initially worse compared to HER2 negative patients, significantly improved after administration of trastuzumab.